Evaluating the property changes of probiotic yogurt fortified with Sidr (Ziziphus spina-christi L.) fruits as functional dairy - Matar, Amal A; Rashed, Nahed; Alhrbi, Alaa S.; Amin, Amin K (Italian Journal of Food Science, 2025)
The development of functional dairy products aligns with the growing demands for health-promoting foods. This study investigates the impact of fortifying probiotic yogurt with varying concentrations of Sidr dried pulp powder (SDPP; 0, 2.5, 5.0, and 7.5%) on its physicochemical, rheological, antioxidant, microbiological, and sensory properties during 15 days of refrigerated storage. The addition of SDPP significantly enhanced the total phenolic and flavonoid contents and the antioxidant activity, while slightly increasing acidity with lowering pH over time. Rheological analysis showed improved viscosity and reduced syneresis at moderate SDPP levels (up to 5%). Microbial viability of Lactobacillus acidophilus and Bifidobacterium bifidum remained within acceptable limits throughout storage. Sensory evaluation indicated that samples fortified with up to 5% SDPP were the most acceptable. These findings suggest that SDPP is an effective functional ingredient in low-fat probiotic yogurt for enhancing nutritional value and sensory appeal.